Formation of BaCrO4 nano crystallites within thermally evaporated sodium bis-2-ethylhexyl-sulfosuccinate and stearic acid thin films - Rautaray, D.; Sinha, K.; Sainkar, S. R.; Pasricha, R.; Pavaskar, N. R.; Sastry, M. (Journal of the American Ceramic Society, 2005)
This paper describes the growth of barium chromate (BaCrO4) nanocrystallites within thermally evaporated thin films of stearic acid (StA) and sodium bis-2-ethylhexyl-sulfosuccinate by a process of Ba2+ ion entrapment followed by in situ reaction CrO42- ions. Dense spherical assemblies of BaCrO4 nanocrystallites of very uniform size (similar to50 nm) were obtained within the two different host matrices. The spherical assemblies were composed of smaller (ca. 5-10 nm size) BaCrO4 crystals indicating that efficient size control over crystal size may be exercised by the matrix. Contact angle measurements of the BaCrO4-StA and BaCrO4-sodium bis-2-ethylhexyl-sulfosuccinate films indicated that they were hydrophobic, thus pointing to the possible role of hydrophobic interaction between the StA and sodium bis-2-ethylhexyl-sulfosuccinate monolayer-covered BaCrO4 crystals in the assembly process.

Fungus-mediated biosynthesis of silica and titania particles - Bansal, Vipul; Rautaray, D.; Bharde, Atul A.; Ahire, Kedar C.; Sanyal, A.; Ahmad, Absar; Sastry, Murali (Journal of Materials Chemistry, 2005)
The synthesis of inorganic materials by biological systems is characterized by processes that occur at close to ambient temperatures, pressures and neutral pH. This is exemplified by biosilicification in marine organisms such as diatoms while laboratory-based synthesis of silica involves extreme temperature and pH conditions. We show here that silica and titania particles may be produced by challenging the fungus Fusarium oxysporum with aqueous anionic complexes SiF62- and TiF62- respectively. Extra-cellular protein-mediated hydrolysis of the anionic complexes results in the facile room temperature synthesis of crystalline titania particles while calcination at 300 degrees C is required for crystallization of silica.